2022
DOI: 10.56314/ijoleh.v1i1.42
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Managerial Strategy in Building Character Education During The Covid-19 Pandemic

Hijrawatil Aswat,
Khaerun Nisa Tayibu,
Satriawati

Abstract: This research aims to analyze various managerial strategies of teachers in instilling character education in children during the Covid-19 pandemic. Research methods of literature review by looking for theoretical references relevant to the case or problem found, namely the managerial strategy of the teacher in strengthening character with the aim as a consideration in choosing and determining the appropriate strategy to use in accordance with its effectiveness and the ability of the teacher to implement it.  T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This study was reinforced by other studies that claimed pedagogical competencies could be identified in concrete terms with other subcategories, such communication and relationship competences or classroom management. According to a study, utilizing teachers' basic pedagogical expertise and specific classroom management skills (Aswat et al, 2022), knowledge as appropriate indicators of their instructional competency. In grouping the pedagogical strategies helped the students take advantage of various learning processes as they develop their sustainability competencies (König et al, 2021;Lozano et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This study was reinforced by other studies that claimed pedagogical competencies could be identified in concrete terms with other subcategories, such communication and relationship competences or classroom management. According to a study, utilizing teachers' basic pedagogical expertise and specific classroom management skills (Aswat et al, 2022), knowledge as appropriate indicators of their instructional competency. In grouping the pedagogical strategies helped the students take advantage of various learning processes as they develop their sustainability competencies (König et al, 2021;Lozano et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…According to Aswat & Tayibu (2022) dan Vergauwe et al, (2021) spontaneous activities are actions taken by students suddenly at that moment, when it is discovered that a student forgets or even intentionally does not pay. In the context of the honesty canteen, spontaneous activities involve a quick response from the canteen manager or school staff to the violations that occur.…”
Section: The Honesty Canteen Program As a Value System In Building St...mentioning
confidence: 99%
“…This entails setting clear schedules, limiting screen time and distractions, incorporating engaging stimuli, addressing physical needs, recognizing small achievements, maintaining open communication with teachers, and seeking support when needed (Caprara & Caprara, 2022). By considering these factors, teachers can create an environment that supports students' academic growth and well-being (Aswat & Tayibu, 2022;Pratiwi & Priyana, 2023).…”
Section: Teaching Approaches In Online Learningmentioning
confidence: 99%
“…As teachers bear significant responsibilities in the execution of online learning and addressing any encountered obstacles, they have been found to be caught unaware of the situation and propelled to develop novel approaches to instruction and education during online classes (An et al, 2021;Howard et al, 2021;Nieto-Escamez & Roldán-Tapia, 2021). For instance, they had to integrate diverse multimedia materials, including videos, audio recordings, and digital textbooks, into their curriculum to effectively involve students and encourage participatory learning (Aswat & Tayibu, 2022;Ferri et al, 2020). Simultaneously, teachers were compelled to employ interactive pedagogical techniques, such as quizzes, polls, and games, to captivate pupils and furnish avenues for formative evaluation to facilitate the students in maintaining their motivation and engagement toward their educational pursuits during the pandemic (Atmojo & Nugroho, 2020;Nieto-Escamez & Roldán-Tapia, 2021).…”
Section: Introductionmentioning
confidence: 99%